Unheard Voices: Analyzing Non-Compliance with the FPIC Principle in Protecting Indigenous Peoples’ Rights in Indonesia - Remal Agungta Ketaren, Saher; Prawira, M. Rizki Yudha (Law Development Journal, 2024)
This study aims to investigate the implementation of the Free, Prior, Informed, and Consent (FPIC) principle as a measure to protect the rights of indigenous communities in Indonesia, by analyzing Decision No. 6/G/LH/2023/PTUN.JPR. In Indonesia, indigenous communities still seem to be overlooked, as their right to make decisions about projects within their traditional territories remains unacknowledged. This situation calls for urgent discussion, as violations of indigenous rights continue to occur, despite such rights are protected by the Constitution of the Republic of Indonesia. This research employs a normative legal approach. The findings, derived from Decision No. 6/G/LH/2023/PTUN.JPR, indicate that the Defendant proceeded to issue the disputed object without facilitating any discussion among the government, company, and the indigenous community. Furthermore, the Second Intervening Defendant failed to include the Plaintiff in the Environmental Impact Assessment (Amdal) process. Additionally, the panel of judges issued a decision that did not adhere to the Guidelines for Adjudicating Environmental Cases. These actions collectively contravene the principle of Free, Prior, and Informed Consent (FPIC), which is mandated by both international and national legal frameworks, underscoring the importance of obtaining consent and ensuring participation from indigenous communities.